Young Lives qualitative fieldwork guide: Round One (2007) - Camfield, L; Crivello, G; Woodhead, M (Young Lives, 2013)
Young Lives is a long-term study of childhood poverty in four developing countries: Ethiopia, India (in the state of Andhra Pradesh), Vietnam and Peru. We are challenging many of the assumptions made about children, both in terms of how they experience poverty and in terms of their roles and capacities as participants in research. We have involved children as young as age 5 in our qualitative research. We maintain that involving them in our research is both ethically and scientifically sound – especially since our research questions focus on the nature and dynamics of childhood poverty. Too often, adult researchers look to adult respondents for all of the answers. It is also assumed that interventions aimed at the household will automatically benefit the children within them. But not all children are the same, and just as they may experience poverty differently from adults, there are also differences and disparities between groups of children. These are important principles guiding Young Lives research with children. This fieldwork guide was produced collaboratively by an international team of researchers taking part in the Young Lives study. The manual guided the first of four planned rounds of data collection in 2007 as part of a longitudinal qualitative research design, woven between rounds of a quantitative household and child survey. The children who participate in this qualitative research were aged 5 to 6 and 12 to 13 at the time, and were recruited from the larger sample of Young Lives children whose lives we have been following since 2002. We plan to visit the same children, families and communities every few years to systematically document and explain changes in their lives. Our qualitative research focuses on everyday experiences of poverty, not only the extreme cases. The various tools described in this guide were designed to encourage the participation of children from a range of backgrounds, along with members of their families and communities. The intention is for the tools to be used flexibly, with the potential for others to adapt them for differing age groups, contexts and research questions. Further information about the design and rationale of this research can be found on the Young Lives website, along with a ‘Guide for Researchers’ and guides for the second round (2008) and third round (2011) of qualitative research.